(untitled) (Tamaddun, 2025)
This study focuses on developing an interactive hybrid book for teaching English to fourth-grade students in inclusive classrooms at SDN 2 Bengkala. The hybrid book integrates digital and print media to accommodate students’ diverse learning needs, particularly those with hearing impairments. Utilizing the ADDIE model, the study followed five phases: Analysis, Design, Development, Implementation, and Evaluation. The book incorporates multimodal content, including sign language videos, text captions, high-contrast images, and interactive elements to enhance engagement and accessibility. The research employed a qualitative descriptive method, gathering data through observations, interviews, and expert validation. The results indicate that the hybrid book significantly improves students’ reading comprehension and engagement by offering interactive features such as quizzes, drag-and-drop exercises, and real-time feedback. Teachers found the book effective in facilitating English learning and inclusive classroom interactions. The study also identified challenges, including limited digital resources and the need for ongoing technological adaptation, which were addressed by ensuring offline accessibility and expert content validation. This research contributes to the field of inclusive education by providing an accessible learning tool that supports diverse student needs. The findings suggest that hybrid books can enhance literacy development and engagement in inclusive classrooms. Future research should explore integrating AI-driven personalized learning and gamified content to further optimize student learning experiences. The study underscores the importance of inclusive educational materials in fostering equitable learning opportunities.